The Wiley handbook of the history and philosophy of criminology - Triplett, Ruth, 1961- (Hoboken : Wiley-Blackwell, 2017)
'A fascinating and informative investigation of criminology theory and practice throughout the centuries and around the world Featuring contributions by distinguished scholars from ten countries, The Wiley Handbook of the History and Philosophy of Criminology provides students, scholars, and criminologists with a truly a global perspective on the theory and practice of criminology throughout the centuries and around the world. In addition to chapters devoted to the key ideas, thinkers, and moments in the intellectual and philosophical history of criminology, it features in-depth coverage of the organizational structure of criminology as an academic discipline world-wide. The first section focuses on key ideas that have shaped the field in the past, are shaping it in the present, and are likely to influence its evolution in the foreseeable future. Beginning with early precursors to criminology$1 (Bs emergence as a unique discipline, the authors trace the evolution of the field, from the pioneering work of 17th century Italian jurist/philosopher, Cesare Beccaria, up through the latest sociological and biosocial trends. In the second section authors address the structure of criminology as an academic discipline in countries around the globe, including in North America, South America, Europe, East Asia, and Australia. With contributions by leading thinkers whose work has been instrumental in the development of criminology and emerging voices on the cutting edge The Wiley Handbook of the History and Philosophy of Criminology provides valuable insights in the latest research trends in the field world-wide - the ideal reference for criminologists as well as those studying in the field and related social science and humanities disciplines'--s
'This book provides students, scholars, and criminologists with a truly a global perspective on the theory and practice of criminology throughout the centuries and around the world. In addition to chapters devoted to the key ideas, thinkers, and moments in the intellectual and philosophical history of criminology, it features in-depth coverage of the organizational structure of criminology as an academic discipline world-wide'--
Introduction / Ruth Ann Triplett -- Key Ideas, Thinkers, and Moments. Criminal Entryways in the Writing of Cesare Beccaria / Matthew P Unger, Jean-Philippe Crete, George Pavlich -- Researching Crime and Criminals in the 19th Century / Peter Becker -- Laughing at Lombroso / Paul Knepper -- Criminology in 19th-Century France / Bruce DiCristina -- Conflict and Crime / Michael J Lynch -- The Extensive Legacy of Symbolic Interactionism in Criminology / Jeffery T Ulmer -- The Chicago School and Criminology / Wim Hardyns, Lieven JR Pauwels -- Anomie, Strain, and Opportunity Structure / Mathieu Deflem -- Differential Association, Differential Social Organization, and White-Collar Crime / John M Eassey, Marvin D Krohn -- The Foundation and Re-emergence of Classical Thought in Criminological Theory / Ray Paternoster, Daren Fisher -- Crime, Deviance, and Social Control / Cesar J Rebellon, Paul Anskat -- The Berkeley School of Criminology / Randolph R Myers, Tim Goddard -- Let Fury Have the Hour / Travis Linnemann, Kyra A Martinez -- Three Strikes and You're Out / John Paul Wright, Kevin M Beaver, Jamie M Gajos, Catherine Sacarellos -- Western Feminist Criminologies / Kaitlyn J Selman, Molly Dunn -- Criminalizing Race, Racializing Crime / Kideste Wilder Yusef, Tseleq Yusef -- Shaming, Reintegration, and Restorative Justice / Hee Joo Kim, Jurg Gerber -- Criminology across the Globe. Criminology in Argentina, 1870-1960 / Ricardo D Salvatore -- Criminology in Australia / Elaine Fishwick, Marinella Marmo -- Criminology in Belgium / Tom Daems, Stephan Parmentier -- Criminology in Brazil / Fernanda Fonseca Rosenblatt, Mar{u2A6C}ia Montenegro Pessoa Mello -- Criminology in Canada / Paul Brantingham, Patricia Brantingham, Bryan Kinney -- Criminology in China / Bill Hebenton, Susyan Jou -- Criminology in Germany and the Gesamte Strafrechtswissenschaft / Kirstin Drenkhahn -- Criminology in Lithuania / Aleksandras Dobryninas -- Criminology in Russia / Olga Semukhina -- Criminology in the United States / Joachim J Savelsberg.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
John Wiley and Sons
Keywords: Criminology -- History; SOCIAL SCIENCE / Criminology; Criminology; History; Electronic books